Cost and management audit - Ramanathan, A. R.; Ramanathan, A. R. (New Delhi : Tata McGraw-Hill Pub. Co., 1989)
A comprehensive practical guide for students and practitioners of cost audit. It lucidly explains the linkage between cost and management audit
Includes index.
Includes bibliographical footnotes.
ucj 16/01/2019
Loans
Keywords: Management audit; Audit